Indonesian dentists knowledge, attitudes and practices in COVID-19 pandemic - Anne Agustina Suwargiani; Erry Mochamad Arief; Asty Samiaty Setiawan; Fidya Meditia Putri; Ardena Maulidia Hamdani; Azlina Nuur Sanjaya; Gilang Yubiliani; Sri Susilawati; Dudi Aripin; Nina Djuastina; Sunardhi Widyaputra (Padjadjaran Journal of Dentistry, 2022)
ABSTRACT